Iluminação no ambiente de trabalho para melhora do humor e alerta em trabalhadores diurnos: revisão sistemática - Pachito, Daniela Vianna [UNIFESP] (2019)
Background: Exposure to light plays a crucial role in biological processes, influencing mood and alertness. Daytime workers may be exposed to insufficient or inappropriate light during daytime, leading to mood disturbances and decreases in levels of alertness. Objectives: To assess the effectiveness and safety of lighting interventions to improve alertness and mood in daytime workers. Methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, seven other databases; Clinical-Trials.gov and the World Health Organization trials portal up to January 2018. We included randomized controlled trials (RCTs), and non-randomized controlled before-after trials (CBAs) that employed a crossover or parallel-group design, focusing on any type of lighting interventions applied for daytime workers. Two review authors independently screened references in two stages, extracted outcome data and assessed risk of bias. We used standardized mean differences (SMDs) and 95%confidence intervals (CI) to pool data from different questionnaires and scales assessing the same outcome across different studies. We combined clinically homogeneous studies in a meta-analysis. We used the GRADE system to rate quality of evidence. Results: The search yielded 2844 references. After screening titles and abstracts, we considered 34 full text articles for inclusion. We scrutinized reports against the eligibility criteria, resulting in the inclusion of five studies (three RCTs and two CBAs) with 282 participants altogether. These studies evaluated four types of comparisons: cool-white light, technically known as high correlated color temperature (CCT) light versus standard illumination; different proportions of indirect and direct light; individually applied blue-enriched light versus no treatment; and individually applied morning bright light versus afternoon bright light for subsyndromal seasonal affective disorder. We found no studies comparing one level of illuminance versus another. We found two CBA studies (163 participants) comparing high CCT light with standard illumination. By pooling their results via meta-analysis, we found that high CCT light may improve alertness (SMD −0.69, 95% CI −1.28 to −0.10; Columbia Jet Lag Scale and the Karolinska Sleepiness Scale) when compared to standard illumination. In one of the two CBA studies with 94 participants there was no difference in positive mood (mean difference (MD) 2.08, 95% CI −0.1 to 4.26) or negative mood (MD −0.45, 95% CI −1.84 to 0.94) assessed using the Positive and Negative Affect Schedule (PANAS) scale. High CCT light may have fewer adverse events than standard lighting (one CBA; 94 participants). Both studies were sponsored by the industry. We graded the quality of evidence as very low. We found one RCT (64 participants) comparing the effects of different proportions of direct and indirect light: 100% direct lighting, 70% direct lighting plus 30% indirect lighting, 30% direct lighting plus 70% indirect lighting and 100% indirect lighting. There was no substantial difference in mood, as assessed by the Beck Depression Inventory, or in adverse events, such as ocular, reading or concentration problems, in the short or medium term. We graded the quality of evidence as low. We found two RCTs comparing individually administered light versus no treatment. According to one RCT with 25 participants, blue-enriched light individually applied for 30 minutes a day may enhance alertness (MD −3.30, 95% CI −6.28 to −0.32; Epworth Sleepiness Scale) and may improve mood (MD −4.8, 95% CI −9.46 to −0.14; Beck Depression Inventory). We graded the quality of evidence as very low. One RCT with 30 participants compared individually applied morning bright light versus afternoon bright light for subsyndromal seasonal affective disorder. There was no substantial difference in alertness levels (MD 7.00, 95% CI −10.18 to 24.18), seasonal affective disorder symptoms (RR 1.60, 95% CI 0.81, 3.20; number of participants presenting with a decrease of at least 50% in SIGH-SAD scores) or frequency of adverse events (RR 0.53, 95% CI 0.26 to 1.07). Among all participants, 57% had a reduction of at least 50% in their SIGH-SAD score. We graded the quality of evidence as low. Publication bias could not be assessed for any of these comparisons. Conclusions: There is very low-quality evidence based on two CBA studies that high CCT light may improve alertness, but not mood, in daytime workers. There is very low-quality evidence based on one CBA study that high CCT light may also cause less irritability, eye discomfort and headache than standard illumination. There is low-quality evidence based on one RCT that different proportions of direct and indirect light in the workplace do not affect alertness or mood. There is very low-quality evidence based on one RCT that individually applied blue-enriched light improves both alertness and mood. There is low-quality evidence based on one RCT that individually administered bright light during the afternoon is as effective as morning exposure for improving alertness and mood in subsyndromal seasonal affective disorder.